The use of a multisensory approach to promote reading in english in a child with dyslexia (2024)
Dyslexia has become a frequent condition that teachers face in classroom settings. However, in public schools, it seems to be more difficult because of the lack of teacher training. As a consequence, some teachers struggle every day in mainstream schools with dyslexic students without the appropriate knowledge to teach them. In this sense, this study describes how teachers deal with this disability when teaching reading in English. The main objective of this qualitative study is to explore how an English teacher accommodates his/her teaching of reading in English to a child with dyslexia, and how multisensory activities could facilitate that process. This case study sample is a sixteen-year-old student diagnosed with dyslexia and a secondary English teacher. Data was collected through observations, interviews, stimulated recalls, and multisensory activities over one scholarly term, this data was analyzed by carrying out a thematic analysis. Findings showed that the use of multisensory activities not only helped dyslexic students overcome difficulties in reading but also increased their motivation towards English classes. Also, the teacher’s role is pivotal when preparing and accommodating his classes taking into account the student’s needs by using multisensory activities. This study supports teachers providing them with the opportunity to explore the use of a multisensory approach for teaching reading in English to dyslexic students.